Development of a framework and tool for the evaluation of the environmental sustainability of public school buildings for disaster evacuation - Armendez, Kevin Jhon Paul Villar
The Philippines is one of the most vulnerable countries to experience disaster-related events, with flooding as the most common case. Affected communities in flood-prone areas are forced to proceed in designated evacuation shelters. Public school buildings (PSB) are typically utilized due to the availability of living space and high accessibility knowledge for evacuating population within any barangay. The aim of this research is to provide a framework and assessment tool for the determination of the sustainability of the school building through evaluation of five factors: Living Space Capacity, Septic Waste Generation, Solid Waste Generation, Accessibility for Disaster Evacuation, and Suitability of Location. Four public school buildings were observed, each measured for sustainability and control variables present within the school building. The assessment tool necessitates input of values and measurements from the assessor involving the control variables that would define the sustainability factors and results from the observed public school building which then can be replicable for other public school building. The tool utilizes sustainability standards and researched constants to perform the desired computation of the assessment tool and then present figures in units corresponding to the input to visualize measured quantities and dimensions that would address the sustainability of the school building. Results show the necessity for the improvement in the facilities of all four public school buildings in the sustainability factors of Solid Waste Generation and Accessibility. The factors for Living Space, Septic Waste Generation and Suitability each obtained only one successful public school building.